PD-1 Gene Polymorphism in Children with Subacute Sclerosing Panencephalitis - İŞCAN, AKIN; Piskin, Ibrahim Etem; Calik, Mustafa; Abuhandan, Mahmut; KOLSAL, Ebru; Celik, Sevim Karakas; Iscan, AKIN (My University, 2013)
Subacute sclerosing panencephalitis (SSPE) is a progressive inflammatory and degenerative disorder of the central nervous system. Several factors influence the risk of chronic brain infection with the mutant measles virus. However, to date, no pathogenic mechanism that may predispose to SSPE has been determined. Studies have indicated that specific polymorphisms in certain host genes are probably involved in impairing the ability of host immune cells to eradicate the measles virus in SSPE patients. Programmed cell death protein 1 (PD-1), a member of the CD28 family, is a negative regulator of the immune system. The purpose of our study was to investigate whether PD-1 gene polymorphisms affect susceptibility to the development of SSPE in Turkish children. In total, 109 subjects (54 SSPE patients and 55 healthy controls) were genotyped for the PD-1.9 C/T (rs2227982) single-nucleotide polymorphism (SNP). The distributions of T alleles in the PD-1.9 polymorphism in SSPE patients and healthy controls were 2.8 and 10.9%, respectively. There was a statistically significant difference between the groups; the 95% confidence interval (CI) was 0.06 to 0.85 and the odds ratio (OR) was 0.23 (chi(2) test). Thus, we identified an association between SSPE and the PD-1 rs2227982 gene polymorphism; the frequency of T alleles was higher in controls than in SSPE patients.